'You don`t realize what you see!': the institutional context of emotional abuse in elite youth sport - Jacobs, F.; Smits, F.; Knoppers, A. (Sport in Society: Cultures, Commerce, Media, Politics, 2017)
Various discourses construct youth sport as a site for pleasure and participation, for positive development, for performance and for protection/safeguarding. Elite youth sport however continues to be a site for emotionally abusive coaching behaviour. Little attention has been paid to how the institutional context may enable or sustain this behaviour. Specifically, how do coaches and directors involved in high-performance women`s gymnastics position themselves in relationship to these discourses to legitimize the ways they organize and coach it? We drew on a Foucauldian framework to analyse the technologies and rationalities used by directors and coaches of elite women`s gymnastics clubs to legitimize and challenge current coaching behaviours. The results of the 10 semi-structured interviews showed how coaches and directors legitimized coaching behaviour using discourses of pleasure, protection, performance and of coaching expertise and assigning responsibility for current coaching behaviour to athletes, parents, (other) coaches and global and national policies.